Hotspot detection in photovoltaic array using thermal imaging method - Mohd Shawal, Jadin; Shahira Farhana, Ahmad Safian; Kamarul Hawari, Ghazali; Ven, Tan Li; Ahmad Syahiman, Mohd Shah (Springer Science and Business Media Deutschland GmbH, 2022)
To maintain the long-term reliability of photovoltaic (PV) modules while maximizing the power output, possible faults in the PV modules need to be diagnosed at an early stage. One of the problems that arise in the PV system is the formation of the hotspot. Numerous hotspot detection methods have been presented over the years to address this issue. This paper presents a non-destructive method based on aerial infrared thermography inspection using a drone for detecting the hotspot in a large-scale PV system. The result shows that the approach can successfully detect the formation of the hotspot in the PV array with overall temperature differences between normal and hotspot cells in the range of 0.6 to 20.4 ℃.